Atenção a disfagia orofaríngea no home care: gerenciamento fonoaudiológico e estudo de validação de aparência e conteúdo de um manual de orientação - Pereira, Karina de Fatima Portela de Oliveira (2015)
The objective of this research was to validate in appearance and contente of the “guidance Manual for adult patientes with dysphagia in speech therapy in home care” orientation directed to patients in fonoaudiologico monitoring.The methodology of its preparation is a mixed study that was divided into three stages being the first building of the manual which was forwarded to two Doctors in the speech area which contributed heeded suggestions for improvement of the material. The second stage was directed in the choice of eight expert judges in the area with master's or doctorate, which evaluated the manual through a questionnaire and the third stage directed to the choice of eight caregivers judges of patients in care Home Care, as a representative population of this study. To analysis the answers of the judges was used Pearson linear correlation and considered valid the answers that obtained correlation higher correlation than 0.6 being this a parameter that represents the existence of strong linear correlation. Among the found results, can be observed through the evaluation of the judges that was possible to improve the instrument, the obtained results by analyzes of the data show the existence of strong correlation bigger than 0.6 in all evaluated questions which demonstrates there is a strong correlation among the questions regarding the contents of the manual data suggesting that the material is valid in appearance and content. It is noteworthy that despite being an instrument easy to use, no need for prior training of the speech therapist for proper use of the material. The study concludes that, taking into account the existence of strong linear correlation, it is understood that the manual was valid in its appearance and content.